Quality of Life in Normal and Overweight Women with Polycystic Ovary Syndrome: A Cross-Sectional Study - Soheila Rabieepoor; Atefeh Yas (Mashhad University of Medical Sciences, 2022)
Background & aim: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women, which is associated with phenotypic changes, fertility disorders and overweight or obesity. Most of women are concerned about the complications of obesity caused by this disease that can adversely affect their quality of life. Therefore, the present study was conducted to compare the quality of life in normal and overweight women with polycystic ovary syndrome.Methods: This was a cross-sectional study which performed on 95 normal and 100 overweight women with polycystic ovary syndrome, who attended two hospitals in Urmia, Iran in 2019 and were selected through convenience sampling. Demographic and quality of life questionnaires for polycystic ovary syndrome were used to collect data.  Independent sample T test and Chi square test were used to analyze the data.Results: The mean age of study participants was 26.93 ±5.37 years. The mean score of total quality of life in women with normal weight and overweight was 137.88 ±13.27 and 99.12 ± 22.15, respectively, which was significantly different (P ≤ 0.001).  Also, the mean score of different areas of quality of life questionnaire, except of menstrual disorders, in overweight women were significantly lower than women with normal weight (P ≤ 0.001). In addition, prevalence of hirsutism in obese women was higher than normal weight women, showing a statistically significant difference (P ≤ 0.001).Conclusion: The results showed that weight gain further reduces the quality of life score in women with polycystic ovary syndrome.